Pentingnya Literasi Budaya dan Kewarganegaraan Terhadap Steriotip Antar Etnis Dalam Mencegah Terjadinya Disasosiasi - Afa Zahra; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Multidisiplin Indonesia, 2023)
Indonesia is a country with extraordinary diversity. "Bhineka Tunggal Ika," the national motto of Indonesia, has been known since ancient times. The diversity of Indonesian culture is a unique wealth not possessed by every nation in the world. This diversity can lead to various perspectives and prejudices among individuals and groups, often arising from the desire to dominate a particular group or ethnicity. In this writing, the researcher conducted a study with the aim of understanding the causes of stereotypes, the reasons for disassociation, and the importance of cultural and civic literacy in preventing ethnic stereotypes. Additionally, the researcher employed a qualitative descriptive method with a qualitative approach, and the data collection technique used in this study was literature review. The results of this research revealed a connection between cultural and civic literacy and ethnic stereotypes, underscoring the importance of such literacy to prevent unfounded and directed stereotypes, thus avoiding national disassociation.